Labor and political subjectivation: epistemological and methodological challenges - Montarcé, Inés (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2019)
The concern to understand the processes of political subjectivation that arise in the heat of contemporary social movements has generated debates in which different theoretical, epistemological and methodological traditions are discussed. In this article we review the contributions of authors inserted in critical currents with the intention of building tools that guide the methodological approach of subjectivities that emerge around concrete experiences of action and labour organization. Finally, these proposals are analyzed considering an empirical research carried out in Mexico City.